Using Statistics in Industry / Quality Improvement Through Total Process Control - Betteley Gordon; Mettrick Neville; Sweeney Edward; Wilson David (Prentice Hall, 1994)
An ideal workplace reference for anyone who needs to improve their understanding of the use of statistics in process control. Introduction, Basics, Data Presentation, Probability and Probability Distributors, The Normal Distribution, Other Probability Distributions, Estimation, Probability Plotting, Process Control, Control Charts, Significance Testing, Advanced Techniques, Qualitative Methods, Bibliography, Subject Index.